2009
DOI: 10.1007/s11240-009-9504-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shoot regeneration in industrial ‘high starch’ sweetpotato (Ipomoea batatas L.) genotypes

Abstract: Sweetpotato (Ipomoea batatas L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…More than 104 million tons are produced globally, 95% of which are grown in developing countries [1]. It is also an alternative source of bioenergy as a raw material for fuel production [2]. The orange-fleshed sweetpotato is rich in beta -carotene, which plays a crucial role in preventing vitamin A deficiency-related blindness and maternal mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…More than 104 million tons are produced globally, 95% of which are grown in developing countries [1]. It is also an alternative source of bioenergy as a raw material for fuel production [2]. The orange-fleshed sweetpotato is rich in beta -carotene, which plays a crucial role in preventing vitamin A deficiency-related blindness and maternal mortality [3].…”
Section: Introductionmentioning
confidence: 99%
“…A higher number of shoots developed from protuberances on a medium containing 5.0 μM TDZ compared to a medium containing 10.0 μM TDZ (Table 1). Gosukonda et al (1995) and Santa-Maria et al (2009) also reported adventitious shoot induction from leaf explants of sweetpotato on a stage II medium, where the explants were incubated for a few days on a medium containing auxins, and were subsequently transferred to a medium supplemented with cytokinins, which resulted in the development of 1-2 shoots per explant with a significant genotype and media interaction. In this study, we obtained relatively few-times more shoots per explant compared to earlier reports Santa-Maria et al, 2009).…”
Section: Production Of Protuberances From Leaf Explantsmentioning
confidence: 96%
“…However, the lack of an efficient regeneration system is the major limiting factor which prevents the development of gene transfer technologies for commercially important cultivars of sweetpotato. There have been a number of proposals for the in vitro propagation of sweetpotato, including via adventitious shoot induction Dessai et al, 1995;Sihachakr et al, 1997;Santa-Maria et al, 2009) and somatic embryogenesis (Liu and Cantliffe, 1984;Chée et al, 1990;Desamero et al, 1994;Bieniek et al, 1995;Zheng et al, 1996;Dhir et al, 1998;He et al, 2009). Genetic transformation of sweetpotato, using various explants, has been reported, but with low efficiency (Newell et al, 1995;Gama et al, 1996;Morán et al, 1998;Okada et al, 2001;Berberich et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For one plant species there exist several genotypes that differ in embryogenesis capacity. It is due to considerable variability of different genotypes in response to hormones . For instance, in the majority of cases frequency of flax embryo development reaches at average as few as 20%, the rest of it is root formation .…”
Section: Introductionmentioning
confidence: 99%